Evaluación de la crioconcervacion de ovocitos en bovino hembra (Boss taurus) en la UA-CAREN en el laboratorio de biotecnología de la reproducción de la carrera de medicina veterinaria y zootecnia de la Universidad Técnica de Cotopaxi - Gutiérrez Cumbajin, Christian Anibal (2015)
This research was conducted at the Laboratory of Reproductive Biotechnology at the Technical University of Cotopaxi in order to assess the cryo preservation of bovine oocytes (Taurus boss) after freezing; This type of conservation technique of cryo oocyte is used as biotechnological tool for breeding of different breeds and improve production through assisted reproduction. The collected oocytes are 20 cows; they were intended to slaughter in the slaughterhouse Saquisilí, preselection for their phenotypic characteristics. The oocytes were removed after slaughter taking into consideration that must be transported quickly to the laboratory to maintain its viability….